Digitalisation as a competitive advantage of Rosatom State Corporation - V. V. Degtyareva; D. A. Murzintseva (Вестник университета)
The article considers the process of digitalisation of the nuclear industry on the example of State Atomic Energy Corporation Rosatom and foreign companies. The purpose of the study is to identify the digital competitive advantages of Rosatom and analyse global competitors. The main prospects and trends in the development of the state corporation have been identified. The article describes the problems faced by the process of digitisation of the industry. The current digital products of Rosatom and its developments have been considered. The positive effects of the Lean Smart Plant project, the introduction of electronic document management have been described. The process of digital transformation includes the introduction of artificial intelligence, a digital twin, the Internet of things, which also changes the methodology of enterprise management and production, the infrastructure sector, high-tech modeling, automation of design and construction. It is stated that digital transformation has a multiplicative effect. The complex use of digital technologies and platforms allows you to reduce logistics costs, increase labor productivity, reduce the level of labor intensity of production and increase KPI. The main conclusions of this article are that there are a number of problems on the way of implementing digitalisation in the nuclear industry that should be overcome using current, modern, including foreign digital services that can positively affect changes due to transformational digital shifts.